Role Of Transformative Leadership In Dealing With Challenges Faced By The Kenyan Public Service - Onyango, Michael Ang’anyo (Advances in Social Sciences Research Journal, 2020)
Leadership on the African continent has been a focus of scholars as African nations have incredible human and natural resources but seem to be bereft of the leaders necessary to capitalize on its opportunities. Researchers acknowledge that the barrier to progress in the developing world is not the deficiency of money or natural resources, but suggested it to be the lack of leadership. Researchers have demonstrated reasons for this deficiency including the effects of the colonial system upon people and civil service systems, but have not yet been able to establish a promising path to economic and social progress. Leaders in Kenya provided promising solutions in the national strategic plan, Kenya Vision 2030, to move it to a first world economy within 25 years. One of the foundations of the plan was public service reform with a flagship project to establish the Kenya School of Government to develop transformative leadership training and fill the leadership gap. The purpose of this workplace individual assignment was to investigate, understand, and describe the role of transformative leadership in dealing with challenges faced by the Kenyan public service. The transformational leadership theory approach of Burns (1978) was used as the locus point for the study. Using a qualitative case study method, secondary data was gathered from relevant literature at the state department of interior – the literature was then reviewed through desk literature review. The result of the analysis was that development of training for transformative leadership was an intentional goal which was seen as critical strategy in dealing with challenges faced by the Kenya public service for national success. The discussion concludes by making recommendations on how to develop a transformative leadership mind-set among public officers. Kenya and other developing countries may benefit from the results of this study as it provides an insight on how leadership is about stepping into the gap, solving problems and unlocking people’s potential for dealing with challenges in the public service.